Channel sedimentation within urban gravel bed rivers - Martin C. Thoms (1987)
Fine substrate sediments are considered to be important in the management of urban river systems. Urban construction activities have been reported to increase sediment loads causing the temporary siltation of channel substrates within the urban area. Nevertheless fine sediment derived from urban areas frequently carry toxic material well in excess of background concentration levels. While the soluble phase of heavy metals and the importance of their association with suspended sediment has received considerable attention, longer term studies of fine urban river-bed sediments are limited. Furthermore studies of heavy pollutants in active stream sediments, below mine waste tips, have shown the channel substrate can provide a long term store for heavy metals in association with fine sediments. This thesis investigates the variety of impacts that urbanisation has upon the sedimentation of gravel bed rivers. A freeze coring technique and infIltration baskets have been used to study the textural-geochemical properties of fme matrix sediment and its development within an urban river-bed framework, within and below a number of contrasting urban catchments in the U.K. Complex urban hydrological and sedimentological regimes are shown to have a variable influence upon matrix sedimentation. The actual volume of matrix present within the urbanised substrate is influenced by the degree of urbanisation within the catchment. Furthermore this sediment is finer in size and associated heavy metal concentrations are well in excess of natural background levels. Although heavy metal levels do correlate slightly with textural characteristics, the presence of maximum concentrations at depth in the substrate indicate possible mobilisation of metals within the urbanised river-bed. The temporal behaviour of matrix development within an urbanised substrate is shown to differ from natural river-beds. Despite high suspended sediment concentrations the magnitude of the potential rate of supply is lower, by 50 percent, and dominated by organic material. This sediment also contains elevated heavy metal cocnentrations. This contrasts to the inorganic sediment ingress of natural river substrates. It is concluded that fine matrix sediments within urban gravel bed rivers should be at least of concern to public health engineers, water authorities and conservationists.